Melanonychia: A Challenging Green Nail Syndrome Case Report - Kyoko Sugioka; Tomoko Akeda; Keiichi Yamanaka (Clinical Case Reports)
ABSTRACT Nail dyschromia caused by Pseudomonas aeruginosa infection, known as Green Nail Syndrome, is a condition occasionally encountered by clinicians. It usually affects one or two nails, but can involve more. Dyschromia may be limited to the nail tip. Treatment with topical nadifloxacin proved to be effective.